Practices related to infection control during COVID-19 times among dental practitioners in Hubli–Dharwad: A cross-sectional survey - Hema Tyavanige Shekharappa; Prathik S Bolaar; Preetha J Shetty (Journal of Indian Association of Public Health Dentistry, 2022)
Background: In view of the global crisis due to the pandemic, dental practitioners are one of the high-risk categories in acquiring and spreading the infection due to their close approximation with the oral cavity. In this regard, dentists play a major role in preventing cross-contamination by following proper infection control protocol. Aim: This study aimed to assess the practices related to infection control protocol regarding COVID-19 among dental practitioners in Hubli–Dharwad. Materials and Methods: A cross-sectional study was conducted between September and October 2020 for 2 months. One hundred and fifteen IDA-registered dental practitioners were randomly selected, and a pretested close-ended questionnaire comprising 28 questions related to infection control practices was distributed. The questions were designed to mimic a usual clinical scenario when the patient walks in for a treatment. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS) version 22, Chi-square test was used to compare the groups, and the value of P was set at P ≤ 0.05. Results: Majority of the practitioners were following the proper infection protocol related to COVID-19. However, the proper method of donning and doffing of personal protective equipment (PPE) (59%) as well as disposal of PPE (56%) was not followed appropriately. A statistically significant difference was observed in relation to the location of the clinic the usage of consent forms (P = 0.017) and performing aerosol-generating procedures (P = 0.016). With respect to the professional years of experience, a statistically significant difference was observed related to the air conditioning of dental clinics (P = 0.031) and the type of filters installed (P = 0.007). Conclusion: Infection control protocol was followed properly by most of the practitioners; however, continuing dental education and short-term courses will add to increased awareness regarding infection control during the times of new infection.